Genotoxic Effect of N-Hydroxy-4-Acetylaminobiphenyl on Human DNA: Implications in Bladder Cancer - Shahab, Uzma; Moinuddin; Ahmad, Saheem; Dixit, Kiran; Habib, Safia; Alam, Khursheed; Ali, Asif (PLOS ONE, 2013)
Background The interaction of environmental chemicals and their metabolites with biological macromolecules can result in cytotoxic and genotoxic effects. 4-Aminobiphenyl (4-ABP) and several other related arylamines have been shown to be causally involved in the induction of human urinary bladder cancers. The genotoxic and the carcinogenic effects of 4-ABP are exhibited only when it is metabolically converted to a reactive electrophile, the aryl nitrenium ions, which subsequently binds to DNA and induce lesions. Although several studies have reported the formation of 4-ABP-DNA adducts, no extensive work has been done to investigate the immunogenicity of 4-ABP-modified DNA and its possible involvement in the generation of antibodies in bladder cancer patients. Methodology/Principal Findings Human DNA was modified by N-hydroxy-4-acetylaminobiphenyl (N-OH-AABP), a reactive metabolite of 4-ABP. Structural perturbations in the N-OH-AABP modified DNA were assessed by ultraviolet, fluorescence, and circular dichroic spectroscopy as well as by agarose gel electrophoresis. Genotoxicity of N-OH-AABP modified DNA was ascertained by comet assay. High performance liquid chromatography (HPLC) analysis of native and modified DNA samples confirmed the formation of N-(deoxyguanosine-8-yl)-4-aminobiphenyl (dG-C8-4ABP) in the N-OH-AABP damaged DNA. The experimentally induced antibodies against N-OH-AABP-modified DNA exhibited much better recognition of the DNA isolated from bladder cancer patients as compared to the DNA obtained from healthy individuals in competitive binding ELISA. Conclusions/Significance This work shows epitope sharing between the DNA isolated from bladder cancer patients and the N-OH-AABP-modified DNA implicating the role of 4-ABP metabolites in the DNA damage and neo-antigenic epitope generation that could lead to the induction of antibodies in bladder cancer patients.